Chimeric Human Liver Reconstruction within the Spleen of Adult Pigs. (July 2018) - Kobayashi, Eiji; Enosawa, Shin
Abstract : Introduction: Because it is difficult to determine its effects compared to liver transplantation, hepatocyte transplantation has not become an established therapeutic method. The problem in the current clinical cases is that, although the vertical portal vein hepatocytes are being transplanted orthotopically, an adequate amount of cells cannot be transplanted. We had reported earlier that liver spheroids transplanted to the mesentery became vacuolized and did not engraft for long time, but those transplanted into the liver stump were able to engraft favorably for a long time. Thus, for hepatocyte proliferation, the choice of the transplant location is extremely important. In this study, by reviewing the intrasplenic hepatocyte transplantation performed earlier by Mito et al ., we have examined the spleen as the engraftment location for human hepatocyte transplantation, using swine models. Materials and Methods: In the first experiment performed in adult swine, hematogenous hepatocyte transplantation was carried out, taking advantage of the swine size. The splenic artery and vein were cannulated and separated from the systemic circulation, so that temporary extracorporeal circulation could be performed. As a pretreatment to attenuate spleen immune-cell activity, perfusion with mitomycin C was performed, followed by a thorough rinsing. Secondly, human hepatocytes were transplanted using this route, after which splenic arteriovenous blood flow was resumed under the triple immunosuppressive drug administration. Results: In the swine model, human serum albumin level was 72.9 ng/ml in the first week after transplantation, after which, although it slightly decreased, it could be detected for one month after transplantation. The macroscopic findings of the spleen after one month of transplantation revealed tissues that can be considered as the transplanted hepatocytes. Furthermore, in the human albumin immunostaining and HE (hematoxylin and eosin) staining, the cells considered to be hepatocytes were positive for human albumin. Discussion: In the proceeding experiment using rat model study, although an intense luminescence was observed in the spleen immediately after transplantation, a considerable amount of cells migrated to the liver, where the luminescence intensity of the spleen did not change over time for 100 days or more. Transplanted hepatocytes were observed and a liver-like construction was formed, even when histological imaging was used to evaluate the engraftment. In most tissues and organs, blood flows from an artery to a vein through capillaries. However, the liver and spleen do not have capillary vessels, but a looser tissue portion called sinusoid or sinusoidal structure. Conclusion: The spleen can be considered as an excellent location for hepatocyte transplantation and enfraftment.